2013
DOI: 10.1063/1.4810927
|View full text |Cite
|
Sign up to set email alerts
|

Random walks on non-homogenous weighted Koch networks

Abstract: In this paper, we introduce new models of non-homogenous weighted Koch networks on real traffic systems depending on the three scaling factors r1,r2,r3∈(0,1). Inspired by the definition of the average weighted shortest path (AWSP), we define the average weighted receiving time (AWRT). Assuming that the walker, at each step, starting from its current node, moves uniformly to any of its neighbors, we show that in large network, the AWRT grows as power-law function of the network order with the exponent, represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…The average weighted receiving time (AWRT) is the sum of mean weighted first-passage times (MFPTs) for all nodes absorpt at the trap located at a given target node 16 17 18 . In 2013, Dai et al introduced the non-homogenous weighted Koch networks depending on the three weight factors 19 . They defined the average weighted receiving time (AWRT) for the first time and studied the AWRT on random walk.…”
mentioning
confidence: 99%
“…The average weighted receiving time (AWRT) is the sum of mean weighted first-passage times (MFPTs) for all nodes absorpt at the trap located at a given target node 16 17 18 . In 2013, Dai et al introduced the non-homogenous weighted Koch networks depending on the three weight factors 19 . They defined the average weighted receiving time (AWRT) for the first time and studied the AWRT on random walk.…”
mentioning
confidence: 99%
“…Based on that work, they developed the non-homogeneous weighted Koch networks [19] and the weighted tetrahedron Koch networks [20]. The average weighted receiving time (AWRT) was defined for the first time in [19]. They introduced a family of deterministic non-homogeneous weighted Koch networks on random walk with three scaling factors (i.e., r 1 , r 2 , r 3 ∈ (0, 1)), and showed that in a large network, the AWRT grows as power-law function of the network order with the exponent, represented by log 4 (1 + r 1 + r 2 + r 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, Dai et al presented weighted Koch networks on weight-dependent walk with one weight factor [18], and developed a multilayered division method to determine the average receiving time (ART). Based on that work, they developed the non-homogeneous weighted Koch networks [19] and the weighted tetrahedron Koch networks [20]. The average weighted receiving time (AWRT) was defined for the first time in [19].…”
Section: Introductionmentioning
confidence: 99%
“…During the past decade, complex network theory is exclusively focused on the single network. [4][5][6][7][8][9][10][11][12][13][14][15][16] In reality, networks rarely appear in isolation, but always are coupled together. Recently, the proposed concepts of interdependent networks and interacting networks mark a turning point in the research field of complex network.…”
Section: Introductionmentioning
confidence: 99%